(untitled) (Regional aspects of productive forces development of Ukraine, 2019)
In the article to consider the issues of energy and environmental modernization of the socio-economic development of the Kupchynets association territorial municipality. The actual problems in these areas, the difficulties faced by the newly formed territorial communities, are outlined, the specific strategic directions that are to be implemented by the community in the area of energy conservation and ecological optimization of the community territory are outlined. The main among them are the authors see educational activities for community management and other stakeholders, implementation of energy management systems in the community, energy audit of objects on the territory of the community, and implementation of measures for the conservation of the environment.